PELATIHAN KETERAMPILAN MASTER OF CEREMONY BAGI WARGA RUSUNAWA MUARA BARU, JAKARTA - Syarief Darmoyo; Sri Hapsari Wijayanti; Dara Arum Hartini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
ABSTRACT Public speaking does not just belong to celebrities; it belongs to all of us. Some of us have problems speaking in public, including the Rusunawa Muara Baru, Jakarta residents. The results of our needs analysis found that Rusunawa residents faced several issues related to public speaking. That was feeling anxious, not confident,